The Impact of Creative Content on Digital Marketing Effectiveness: A Comprehensive Analysis - Yuniarti, Yuniarti; Aziz, Muhammad; Gani, Hamsu Abdul (International Journal of Scientific Research and Management (IJSRM), 2024)
Digital marketing has become one of the most sought-after mediums by the general public and businesses today. This marketing method allows for an expanded market reach, faster communication, and ease in transaction processes. This research aims to investigate and describe the relationship between the level of creativity in a company's digital marketing strategy and its success in achieving marketing goals, such as increased website traffic, customer conversions, or product sales. This study adopts a qualitative approach, with data collected through interviews with respondents as the primary method. A literature review is also used to obtain theoretical or secondary data in this research. The literature review involves researching books, literature, and official documents relevant to the research topic. The research results indicate that creativity in digital marketing plays a crucial role in achieving marketing success. Entrepreneurs must possess entrepreneurial creativity that enables them to create or modify new ideas in running their businesses. The steps in digital marketing assist companies in promoting and marketing their products or services more effectively. Another advantage is the ability to convey information to consumers more rapidly and efficiently regarding geographical reach and communication methods. This research has significant implications for companies looking to enhance their digital marketing performance. Companies can develop more effective approaches to achieve their marketing objectives by understanding the importance of creativity in digital marketing strategies. Additionally, the results of this research can serve as a foundation for further studies in this field and contribute to a better understanding of the role of creativity in digital marketing success.